Medical School Attrition-Beyond the Statistics A Ten Year Retrospective Study - Maher, Bridget M (BioMed Central, 2013)
BACKGROUND: Medical school attrition is important - securing a place in medical school is difficult and a high attrition rate can affect the academic reputation of a medical school and staff morale. More important, however, are the personal consequences of dropout for the student. The aims of our study were to examine factors associated with attrition over a ten-year period (2001–2011) and to study the personal effects of dropout on individual students. METHODS: The study included quantitative analysis of completed cohorts and qualitative analysis of ten-year data. Data were collected from individual student files, examination and admission records, exit interviews and staff interviews. Statistical analysis was carried out on five successive completed cohorts. Qualitative data from student files was transcribed and independently analysed by three authors. Data was coded and categorized and key themes were identified. RESULTS: Overall attrition rate was 5.7% (45/779) in 6 completed cohorts when students who transferred to other medical courses were excluded. Students from Kuwait and United Arab Emirates had the highest dropout rate (RR = 5.70, 95% Confidence Intervals 2.65 to 12.27;p < 0.0001) compared to Irish and EU students combined. North American students had a higher dropout rate than Irish and EU students; RR = 2.68 (1.09 to 6.58;p = 0.027) but this was not significant when transfers were excluded (RR = 1.32(0.38, 4.62);p = 0.75). Male students were more likely to dropout than females (RR 1.70, .93 to 3.11) but this was not significant (p = 0.079). Absenteeism was documented in 30% of students, academic difficulty in 55.7%, social isolation in 20%, and psychological morbidity in 40% (higher than other studies). Qualitative analysis revealed recurrent themes of isolation, failure, and despair. Student Welfare services were only accessed by one-third of dropout students. CONCLUSIONS: While dropout is often multifactorial, certain red flag signals may alert us to risk of dropout including non-EU origin, academic struggling, absenteeism, social isolation, depression and leave of absence. Psychological morbidity amongst dropout students is high and Student Welfare services should be actively promoted. Absenteeism should prompt early intervention. Behind every dropout statistic lies a personal story. All medical schools have a duty of care to support students who leave the medical programme.